Characteristics of Child Perpetrators of Violence with Substance Use Disorders at Grhasia Psychiatric Hospital, Yogyakarta - Niufti Ayu Dewi Mahila; Alya Safira Maharani (Universitas Ahmad Dahlan, 2026)
Background: Children who perpetrate violence in the context of substance use disorders constitute a high-risk subgroup requiring a comprehensive understanding of their clinical and social characteristics to inform effective prevention and intervention strategies. In Indonesia, evidence describing the profiles of child perpetrators of violence within specialized mental health services, including psychiatric hospitals, remains limited. This study aimed to describe the demographic and clinical characteristics, patterns of substance use, and associated risk factors among child perpetrators of violence treated or examined at Grhasia Psychiatric Hospital between 2018 and 2022. Methods: A retrospective descriptive study was conducted using medical records of child patients (≤18 years) identified as perpetrators of violent acts and diagnosed with substance use disorders at Grhasia Psychiatric Hospital from 2018 to 2022. Variables analyzed included age, sex, and types of substances used. Results: Of the eligible cases, most child perpetrators of violence with substance use disorders were male adolescents aged 11–18 years (82.35% and 94.11%, respectively). These findings indicate that male adolescents represent the most vulnerable group for involvement in violence associated with substance use disorders within psychiatric service settings. Conclusion: Substance-related violence among adolescents represents a substantial public health burden. The predominance of male adolescents among violent child perpetrators underscores the need for targeted, multidisciplinary prevention and intervention strategies, alongside strengthened psychiatric health information systems to support effective clinical management and evidence-based policy development.